Herpesviruses 6 and 7 types: the view of a pediatrician - Zh. L. Malakhova; L. A. Perminova; E. A. Kashuba; E. N. Kolokoltseva; A. V. Tarasov (Журнал инфектологии)
Herpetic diseases are widespread among cancer patients and are of interest to specialists in various fields. It is herpetic infections that are often common among cases of infant mortality. The main causative agents of herpetic phenomena in humans are manifested by the 8 most studied types of the virus. The article presents a review of modern scientific literature on herpetic diseases caused by herpes viruses 6 and 7. The issues of the history of the study of diseases, etiology, features of the distribution, the pathogenesis of diseases, a wide manifestation of manifestations in childhood, diagnosis, and tactics of managing patients are outlined.